The genus Ptychoceras d'Orbigny in the Aptian-Albian of Patagonia and Antarctica - Riccardi, Alberto Carlos; Medina, Francisco Alberto (Neues Jahrbuch für Geologie und Paläontologie - Abhandlungen)
Aptian - Albian Ptychoceratidae of southern Patagonia and James Ross Island, Antarctica are described. They are represented by Ptychoceras adpressum (J. SOWERBY, 1814), P. forbesianum STOLICZKA, 1865 and P. hamaimense PERVINQUIÈRE 1907. P. hamaimense occurs in the Peltocrioceras deeckei Assemblage Zone (Upper Aptian) of Patagonia and the Pictetia Assemblage Zone (Lower Albian) of Antarctica. P. adpressum has been recorded from the Upper Albian Puzosia vegaensis Assemblage Zone of Patagonia and Tetragonites Assemblage Zone of Antarctica. P. forbesianum occurs in the Middle-Late Albian of Antarctica. Fil: Riccardi, Alberto Carlos. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleozoología Invertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Medina, Francisco Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires; Argentina